2021
DOI: 10.1186/s13071-021-05050-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial composition of midgut and entire body of laboratory colonies of Aedes aegypti and Aedes albopictus from Southern China

Abstract: Background Aedes aegypti and Aedes albopictus are invasive mosquito species and significantly impact human health in southern China. Microbiota are confirmed to affect the development and immunity of mosquitoes. However, scientists have focused more on midgut microbiota of female mosquitoes and bacterial differences between female and male Aedes mosquitoes. The relationship between the midgut and entire body microbiota of Aedes is unclear. In this study, we collected mosquito samples reared und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 77 publications
(69 reference statements)
1
11
0
Order By: Relevance
“…The populations of symbiotic microbes changed depending on the species, period, and diet of the mosquito ( Wang et al, 2011 ; Vogel et al, 2017 ). The main phyla of the A. albopictus microbiota were Proteobacteria, Ascomycota, Bacteroidetes, and Firmicutes, all of which had been similarly reported in other mosquito species ( Pidiyar et al, 2004 ; Rani et al, 2009 ; Boissiere et al, 2012 ; Lin et al, 2021 ). Among the Proteobacteria phylum, two genera, Wolbachia and Serratia , were most associated with mosquitoes; Wolbachia stimulates the production of reactive oxygen species and activates the immune system in the body, resulting in the production of antimicrobial peptides to fight viruses ( Pan et al, 2012 ; Mains et al, 2016 ).…”
Section: Discussionsupporting
confidence: 62%
“…The populations of symbiotic microbes changed depending on the species, period, and diet of the mosquito ( Wang et al, 2011 ; Vogel et al, 2017 ). The main phyla of the A. albopictus microbiota were Proteobacteria, Ascomycota, Bacteroidetes, and Firmicutes, all of which had been similarly reported in other mosquito species ( Pidiyar et al, 2004 ; Rani et al, 2009 ; Boissiere et al, 2012 ; Lin et al, 2021 ). Among the Proteobacteria phylum, two genera, Wolbachia and Serratia , were most associated with mosquitoes; Wolbachia stimulates the production of reactive oxygen species and activates the immune system in the body, resulting in the production of antimicrobial peptides to fight viruses ( Pan et al, 2012 ; Mains et al, 2016 ).…”
Section: Discussionsupporting
confidence: 62%
“…Consistent with prior research, the bacterial composition of Ae. albopictus was predominantly governed by the Wolbachia genus (Lin et al, 2021). When Wolbachia infection is highly dominant, it can “mask” the DNA of other bacteria present (Minard et al, 2014; Bennett et al, 2019) leading to undetected and unsequenced sequences.…”
Section: Discussionmentioning
confidence: 99%
“…This highly dominant infection by Wolbachia in both populations may be related to interactions between microbiome components, such as interspecific competition for resources (Brinker et al, 2019; Scolari et al, 2019) but also to laboratory rearing conditions (Lin et al, 2021). Research into the microbiota of laboratory and wild Aedes mosquitoes has revealed that both are primarily characterized by a limited number of phyla (Scolari et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing results were analyzed using the QIIME2 pipeline. Non-metric multidimensional scaling (NMDS) was performed to evaluate change in beta diversity of gut microbiota based on the Bray-Curtis distance ( 18 ). Differential taxa were identified using the linear discriminant analysis effect size (LEfSe) ( 19 ).…”
Section: Methodsmentioning
confidence: 99%